Out-of-School Children in Pakistan: A Comparative Gender Analysis of Boys and Girls - Dr. Sumera Imran; Dr. Zahid Ullah; Maria Gogosh; *Dr. Abid Khan; Safa Bibi (Social Science Review Archives, 2025)
Pakistan continues to face a severe educational crisis, with millions of children outside the formal schooling system. The education ministry has presented alarming statistics, revealing that 26,206,520 children are currently out of school across the country. In Khyber Pakhtunkhwa out-of-school children reach 4.92 million. Among the out-of-school children, 53 % are girls and 47% are boys. Gender disparity is a persistent challenge, particularly in rural districts. This study provides a comparative analysis of out-of-school boys and girls, focusing on Mardan and Swat districts of Khyber Pakhtunkhwa. A qualitative approach was employed for data collected from 10 secondary school teachers (5 male teachers from Mardan and 5 female teachers from Swat). Findings reveal that girls face socio-cultural restrictions, early marriage, household responsibilities, and infrastructure deficits, while boys are more affected by economic pressures, child labour, and peer influence. Teacher responses provide nuanced insights into district-specific barriers. The study concludes with recommendations for gender-specific, context-sensitive interventions to reduce out-of-school children (OOSC) in Pakistan.